You should use the following trigonometric identities, such that:

`1 + tan^2 x = 1/(cos^2 x) => 2 + tan^2 x = 1 + 1/(cos^2 x)`

`1 + cot^2 x = 1/(sin^2 x) => 2 + cot^2 x = 1 + 1/(sin^2 x)`

Replacing ` 1 + 1/(cos^2 x)` for `2 + tan^2 x` and `1 + 1/(sin^2 x)` for `2 + cot^2 x` yields:

`(1 + sin^2 x)/(1 + 1/(sin^2 x)) + (1 + cos^2 x)/(1 + 1/(cos^2 x)) = (sin^2 x(1 + sin^2 x))/(1 + sin^2 x) + (cos^2 x(1 + cos^2 x))/(1 + cos^2 x)`

Reducing duplicate factors yields:

`(1 + sin^2 x)/(1 + 1/(sin^2 x)) + (1 + cos^2 x)/(1 + 1/(cos^2 x)) = sin^2 x + cos^2 x`

Using Pythagorean identity yields:

`(1 + sin^2 x)/(1 + 1/(sin^2 x)) + (1 + cos^2 x)/(1 + 1/(cos^2 x)) = 1`

**Hence, evaluating the given expression, under the given conditions, yields **`(1 + sin^2 x)/(2 + cot^2 x) + (1 + cos^2 x)/(2 + tan^2 x) = 1.`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now